Deskripsi berpikir tingkat tinggi siswa SMP dalam menyelesaikan soal PISA konten change and relationship - Mochamad Hendri Kusuma; Novisita Ratu (STKIP PGRI Banjarmasin, 2018)
This research is a qualitative descriptive which aims to determine how junior high school students’ higher order thingking skill to solve PISA mathematical problems on change and relationship content. Subjects in this research were two grade IX students of SMP N 1 Salatiga on academic year 2018/2019 who had high mathematical skill. Data collecting methods in this research are test, interview, and documentation. This research uses data reduction, data display and conclusion drawing in data analyzing. Based on the results of the analysis are gained (1) subject INA and subject PSP can achieve all level of higher order thinking starting from analyzing (C4), evaluating (C5), and creating (C6), (2) the two subject show different solving in the C5 and C6 problems but there’s no difference for the C4 problems. This research is expected to provide an overview for the teacher, especially in mathematics learning about students’ higher order thinking level that teachers are able to apply learning strategies which appropriate to students' thinking skills.